Role of scatter-hoarding rodents in the seed dispersal of large-seeded plants. - Low, Gerard Hongkai. (2013)
Large animals are believed to have coevolved to become the primary dispersers of large-seeded plants. With the deforestation that usually accompanies agriculture and urbanization, habitats for large animals have been significantly reduced or lost, leading to the eventual disappearance of such animals. With the loss of these primary dispersers, large-seeded plants require other means of dispersal if they are to propagate and survive. One such mode of dispersal is via secondary dispersal by scatter-hoarding seed-predating rodents. Our study explored three areas: 1) the extent to which small mammals were able to serve as secondary dispersers of large seeds, 2) the difference in such dispersal activity between primary rainforests and secondary rainforests, and 3) the possible viability of seeds in the aftermath of seed predation. Our results have shown that while small mammals such as the plantain squirrel can serve as secondary dispersers of large seeds, there seems to be a lack of secondary seed dispersal activity in the secondary rainforest, and a distinct lack of scatter-hoarding rodents such as squirrels in the secondary forest area compared to the primary forest. Also, our study shows that seeds are able to withstand considerable amount of damage to the endosperm and cotyledons, and still retain viability as long as the embryo is still intact.